SOXopathies: Growing Family of Developmental Disorders Due to SOX Mutations. Issue 9 (September 2019) - Angelozzi, Marco; Lefebvre, Véronique
Abstract : The SRY-related (SOX) transcription factor family pivotally contributes to determining cell fate and identity in many lineages. Since the original discovery that SRY deletions cause sex reversal, mutations in half of the 20 human SOX genes have been associated with rare congenital disorders, henceforward called SOXopathies. Mutations are generally de novo, heterozygous, and inactivating, revealing gene haploinsufficiency, but other types, including duplications, have been reported too. Missense variants primarily target the HMG domain, the SOX hallmark that mediates DNA binding and bending, nuclear trafficking, and protein–protein interactions. We here review key clinical and molecular features of SOXopathies and discuss the prospect that the disease family likely involves more SOX genes and larger clinical and genetic spectrums than currently appreciated. Highlights: SOXopathies are rare, severe disorders resulting from mutations in the SOX genes. They have been associated to date with half of the 20 SOX family members and the numbers of genes involved and pathogenic variants are still on the rise. Most SOXopathies result in developmental defects and are syndromic, including such severe defects as sex reversal, intellectual disability, skeletal dysmorphism, and cardiovascular anomalies. SOXopathies can be caused by many types of gene alterations, and most mutations are de novo, heterozygous, and loss-of-function, thus exposing gene haploinsufficiency. Missense variants are almost exclusively located in the HMG domain, a distinctive and multifunctional feature of all SOX proteins.